Social Distancing Policy and Responses by Indonesian Muslim Intellectuals - Napsiah, Napsiah (el Harakah: Jurnal Budaya Islam, 2021)
The Covid-19 pandemic has affected Muslim religious practices. Social distancing policy, which requires not to gather for any activities, are contradictory to the Muslim’s religious ritual which promotes congregational worship. It accidentally becomes concerns of Muslim intellectuals. Therefore, they publish their thoughts in either national or international journals. This article focuses on the results of the intellectual thoughts published in national journals. It employs descriptive qualitative method through journal searches. There are 16 related journals deemed to meet the requirements. The results of the study show that the social distancing policy is responded in pros and cons. Those who go with cons do not intend to refuse the government policies but to purely adhere to religious tenet because religion has long been believed while Covid-19 is perceived as a threat. In this sense, they are afraid of religion more than the Covid-19. Meanwhile, those who are pro are subject to not only government regulations but also religion. Therefore, the Covid-19 pandemic has brought about an adaptive attitude of Muslims to remain obedient to the government regulations by carrying out independent religious practices or through virtual spaces. Pendemi Covid-19 telah berdampak pada praktik keagamaan umat Islam. Kebijakan Social Distancing yang menghendaki tidak berkumpul, bertentangan dengan ritual umat Islam yang mewajibkan ibadah berjemaah. Inilah menjadi daya tarik kaum intelektual. Oleh karena itu, mereka mempublikasikan pemikirannya di berbagai jurnal baik internasional maupun nasional. Artikel ini berfokus pada hasil pemikiran intelektual yang dipublikasikan di jurnal nasional. Penelitian kualitatif deskriptif  diperoleh melalui penelusuran jurnal, terdapat 16 jurnal bertema Islam yang dianggap memenuhi persyaratan. Hasil pemikiran kaum intelektual menunjukkan bahwa Kebijakan Social Distancing direspons pro dan kontra. Golongan yang kontra dalam hal ini bukan menolak kebijakan pemerintah tetapi lebih pada menunjukkan ketaatan pada agama yang jauh sebelumnya diyakini, sedangkan Covid-19 adalah ancaman. Dalam posisi ini mereka lebih takut pada agama daripada Covid-19. Sedangkan yang pro tidak hanya tunduk pada peraturan pemerintah, tetapi juga tunduk pada agama. Dengan demikian, pandemi Covid-19 membawa sikap adaptif umat Islam untuk tetap patuh pada peraturan pemerintah dengan menjalankan praktik keagamaan secara mandiri atau melalui ruang virtual.